ANALISIS PERTIMBANGAN HUKUM PENGADILAN NEGERI DALAM PERKARA NO.12/PDT.P/2022/PN PTK BERDASARKAN UNDANG-UNDANG PERKAWINAN NOMOR 1 TAHUN 1974 - SALSABILA NIM. A1011191036 (Fakultas Hukum Universitas Tanjungpura, 2023)
ABSTRACTInterfaith marriages generally have the potential to cause legal problems. Both for husband and wife, as well as for third parties, in this case children. However, despite causing problems, the practice of interfaith marriage still occurs in Indonesian society. This happens because of the high interaction of citizens in Indonesia, whose citizens are plural. In practice, there are several ways to deal with interfaith marriages, one of which is to ask for a court decision. From the explanation above, the researcher formulates the problem as follows